Yoga Practice Increases Minimum Muscular Fitness in Children with Visual Impairment - Mohanty, Soubhagyalaxmi (J Caring Sci, 2015)
Introduction: Muscle strength, a component for balance, gait and functional mobility is vital for children with visual impairment. Yoga has frequently been demonstrated to improve physical and mental fitness in children. This study aimed to assess the effect of 16 weeks yoga training on muscular ﬁtness in children with visual impairment. Methods: This was a wait-listed two-armed-matched case–control study. Eighty (41 yoga, 39 control) visual impairment students of both genders aged 9-16 years matched on age, gender and degree of blindness were assessed at pre, mid (after 8 weeks) and post (after 16 weeks) yoga intervention using the Kraus-Weber test. Results: The percentage of students passed in yoga group were 12.2%, 43.9% and 68.3% whereas percentages in the control group were 23.1%, 30.8% and 30.8% in pre, mid, and post tests respectively. McNemar test showed significant differences between pre and mid, mid and post in the yoga group while those parameters were not significantly different in the control group. Yoga therapy seemed to have considerable benefits for the children’s muscular ﬁtness. Conclusion: The study suggests that yoga have considerable benefits for improvement of fitness level in children with visual impairment and may be recommended as and effective, alternative, inexpensive low risk training activity option for them.